Library Management at Batik I Senior High School of Surakarta - Falah, Irfan Fajrul; , Prof. Dr. Sutama, M.Pd; , Dr. Phil. Dewi Candraningrum, M.Ed (2013)
The objectives of this research are four. (1) To describe human resources management at Batik I Senior High School Library of Surakarta; (2) To describe the management of collection at Batik I Senior High School Library of Surakarta; (3) To describe the management of services at Batik I Senior High School library of Surakarta; (4) To describe the room design at Batik I Senior High School Library of Surakarta. It is a qualitative research using ethnography design. It is conducted at Batik I Senior High School Library of Surakarta. The main subject of this study involves library staff (Coordinator, administration), Principal, teachers and students. Data collection technique uses in-depth interview, observation and documentation. Data analysis is started from (1) data collection; (2) data reduction; (3) data display and (4) drawing conclusion. The result of this research includes (1) Human Resource at Batik I Senior High School Library of Surakarta is consisted of three persons -library coordinator, administration and technical staff. The mechanism of hiring the library coordinator is based on open recruitment. (2) The management of collections at Batik I Library includes two main activities namely procurement and processing library materials. (3) The Services available at Batik I Senior High School Library are circulation, reference and internet service. Circulation service uses opened system for loaning and semi closed system for returning. (4) The room design at Batik I Senior High School Library of Surakarta consider the user's comfort. It is divided into three parts, administration room, collection room and reading room. Reading room is equipped by several computers where the students can access the internet to find informatio n.